Ioduria and type 1 diabetes mellitus – Relationships to selected clinical markers of diabetes in adults - Vosátková, Michala; Janíčková Žďárská, Denisa; Zamrazil, Václav; Salátová, Martina; Hill, Martin; Vondra, Karel (Journal of Applied Biomedicine, 2017)
There is a lack of data on the state of iodine reserves and the possible consequences of iodine deficits in diabetic patients. The main aims of this study were to: a) obtain information about iodine saturation in patients with type 1 diabetes; b) determine to what extent this saturation differs from the non-diabetic population; and c) determine whether iodine levels are related to several clinical and laboratory parameters characteristic of diabetic syndrome, including thyroid status. Subjects and methods: A total of 54 males and 51 females treated for type 1 diabetes mellitus (DM1) were included in this cross-sectional study. In addition to iodine saturation determined as the concentration of iodine in the first urine sample of the day, we measured clinical, anthropometric, and biochemical parameters in relation to DM1. Results: Measured iodine levels were: median 152 μg/l, first quartile 117 μg/l, and third quartile 219 μg/l. More than 50% of iodine levels varied within the optimal saturation range of 100–200 μg/l, while about 14% showed incomplete saturation (<100 μg/l), and 34% had increased saturation (>200 μg/l). Multi-dimensional regression showed significant positive relationships; (an OPLS model explaining 9% of the variability) between ioduria and male sex, body weight and height, and serum creatinine levels, which to date have not yet been published. Relationships to the other analyzed parameters (glycated hemoglobin, insulin dose, DM duration, body mass index, microalbuminuria, glomerular filtration rate, thyroid function and volume, thyroid autoimmune markers) were not significant. Conclusions: Iodine saturation levels in our study group were within the ICCIDD (WHO) recommendations for optimal/good saturation for the non-diabetic population, and patients with diabetic syndrome did not differ with respect to the chosen normal ioduria concentrations, i.e. 100 or 150 μg/l. The question remains, however, whether past attempts to deal with iodine deficits in the Czech Republic are responsible for this satisfactory iodine status of the type 1 diabetic population, or if there are other factors involved.
Keywords: dospělí; Iodine; hodnoty glomerulární filtrace; Humans; Creatinine; albuminurie; Iodide Peroxidase; mužské pohlaví; Adult; Autoantibodies; Thyrotropin; jodidperoxidasa; Diabetes Mellitus, Type 1; jod; Albuminuria; autoprotilátky; diabetes mellitus 1. typu; thyreotropin; ženské pohlaví; lidé; kreatinin; Glomerular Filtration Rate; Male; Female